Scientists, institutions and the social nature of international collaboration: the accumulation of social capital in a system of social exchange. Issue 3 (2nd September 2021) - Turpin, Tim; Niu, Xiao
ABSTRACT: International scientific collaboration is widely considered a driver of innovation. However, the social processes through which this can occur are complex. It is not only scientists that have a direct interest in international collaboration; but also the institutions or firms that employ them and the governments whose policies are designed to promote collaboration. This article seeks to reveal the social dynamics underpinning this process. Drawing on an empirical study of 79 scientists working in Australia and China we argue that the social process is essentially a system of exchange . Throughout this system, a range of scientific, innovation and social currencies are offered, received and reciprocated. Through the exchange process, scientific and technological capital is accumulated as different expectations are fulfilled and reconciled. Anthropological and sociological literature offers a theoretical framework for the analysis and the findings offer a sociological perspective of scientific collaboration across national innovation systems.